2021
DOI: 10.1002/adfm.202102843
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Photocatalysts: Pinning Single Atom Co‐Catalysts on Titania Nanotubes

Abstract: Single atom (SA) catalysis, over the last 10 years, has become a forefront in heterogeneous catalysis, electrocatalysis, and most recently also in photocatalysis. Most crucial when engineering a SA catalyst/support system is the creation of defined anchoring points on the support surface to stabilize reactive SA sites. Here, a so far unexplored but evidently very effective approach to trap and stabilize SAs on a broadly used photocatalyst platform is introduced. In self-organized anodic TiO 2 nanotubes, a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 48 publications
4
63
0
Order By: Relevance
“…Note that the above definition [35,37] deviates from methods used in photocatalysis. [46] The Pt SA density was directly determined from the HAADF-TEM images, while also considering the reactive area to be represented by the illumination area (%1 cm 2 ).…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the above definition [35,37] deviates from methods used in photocatalysis. [46] The Pt SA density was directly determined from the HAADF-TEM images, while also considering the reactive area to be represented by the illumination area (%1 cm 2 ).…”
Section: Supporting Informationmentioning
confidence: 99%
“…[29,35,36] Desired defects may either be intrinsically present in some substrates as a result of the synthesis procedure or can be introduced by defect engineering. [33,37,38] More recently, we reported that SAs can be attached to TiO 2 surfaces by trapping at suitable substrate defects. [29] Intrinsic defects of Ti 3þ -O v on TiO 2 nanotubes favor the stabilization of the isolated Pt atoms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhou et al showed that anodic growth of TiO 2 nanotubes poses a considerable strain on tube walls ensuing the formation of the high density of Ti 3+ -O v surface defects. 404 Taking advantage of defect-rich surface they pinned Ir SA sites by a simple impregnation approach. The resulting 0.58% IrSA TiO 2 catalyst displayed a turnover frequency of 4 × 10 6 h −1 .…”
Section: Photoactive Sacs For Ch 4 Ormentioning
confidence: 99%
“…[ 32,33 ] In contrast to these approaches, we recently reported that SA trapping can be achieved on defect‐engineered TiO 2 layers [ 34–36 ] or defects of TiO 2 nanotubes grown by anodization on Ti metal. [ 37–39 ]…”
Section: Introductionmentioning
confidence: 99%